2018
DOI: 10.1021/acs.langmuir.8b00953
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Highly Electroactive Oligoanilines from a p-Aminodiphenylamine/Aniline Mixture with Anionic Vesicles as Templates

Abstract: Oligoanilines with characteristic properties of the electrically conductive emeraldine salt form of polyaniline (PANI-ES) are promising molecules for various applications. A mixture of such oligoanilines can be obtained, for example, enzymatically under mild conditions from the linear aniline dimer p-aminodiphenylamine (PADPA) with hydrogen peroxide (HO) and low amounts of horseradish peroxidase (HRP) in an aqueous pH = 4.3 suspension of anionic vesicles formed from AOT, the sodium salt of bis(2-ethylhexyl)sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Nevertheless, the HPLC analysis turned out to be very useful for analyzing the enzymatic oxidation and oligomerization of PADPA, as a complementary method to the in situ UV/vis/NIR, EPR, and Raman spectroscopy measurements. 2124…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nevertheless, the HPLC analysis turned out to be very useful for analyzing the enzymatic oxidation and oligomerization of PADPA, as a complementary method to the in situ UV/vis/NIR, EPR, and Raman spectroscopy measurements. 2124…”
Section: Results and Discussionmentioning
confidence: 99%
“…23 Recently, it was shown that this phenazinetype units formation can be reduced signicantly by running the reaction instead of PADPA alone with a mixture of PADPA and aniline. 46 By using TvL/O 2 and PADPA in the presence of AOT vesicles, the amount of TvL required to reach high conversion of PADPA into the desired oligomeric PANI-ES-like products, one apparently minor detail is important to be taken in account. It is the way how the aqueous "pH ¼ 3.5 solution" is prepared from a solution of NaH 2 PO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…6A). The lower absorbance at 500-600 nm most likely indicates a lower content of products containing phenazine units if the reaction is run at T ¼ 5 C instead of T ¼ 25 C. 23,46 Overall, there was no indication of a signicant improvement of the products distribution by running the reaction at T ¼ 5 C instead of room temperature. This nding is in contrast to what we had observed previously for the oxidation and polymerisation of aniline in the presence of AOT vesicles with TvL/ O 2 at pH ¼ 3.5 (ref.…”
Section: Effect Of Decreasing the Reaction Temperature Frommentioning
confidence: 97%
“…19,20,[39][40][41][42][43] Several reports have shown data about the vesicle formation but use different methodologies to prepare them (such as extrusion). [44][45][46][47][48][49] Therefore, the chemical structure of the cationic components in the new surfactants strongly impact their aggregation process. 19,20,49 As a complementary experiment, zeta potential measurements were carried out.…”
Section: Determination Of the Microviscosity Of Vesicle Bilayermentioning
confidence: 99%